Extra oxygen and carrier distribution in CuO₂ layers in HgBa₂Can₋₁CunO₂n₊₂₊δ compounds (n=1,2,4) - Lutciv, R.V.; Boyko, Ya.V. (Condensed Matter Physics, 1999)
It is proposed to determine the equilibrium state of the crystal lattice by minimizing the total energy in order to elucidate the role of electrostatic interactions as well as to determine the nonstoichiometry in Hg-contained high temperature superconductors (HTSC). The approximation of non-interacting holes is used to evaluate the band energy. Such an approach enables us to satisfactorily describe the changes of oxygen nonstoichiometry and to indicate the preferred localization of the carriers on oxygen sites in CuO₂ layers.